2019
DOI: 10.3389/fnmol.2018.00496
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Modulators of the Circadian Molecular Clock With Implications for Neuropsychiatric Diseases

Abstract: Circadian rhythms regulate many biological processes and play fundamental roles in behavior, physiology, and metabolism. Such periodicity is critical for homeostasis because disruption or misalignment of the intrinsic rhythms is associated with the onset and progression of various human diseases and often directly leads to pathological states. Since the first identification of mammalian circadian clock genes, numerous genetic and biochemical studies have revealed the molecular basis of these cell-autonomous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 106 publications
0
18
0
Order By: Relevance
“…NOB is among a growing list of small molecules that were identified to directly target the circadian machinery [64,65,66,67,68]. A subset of these clock modifiers have been applied to disease models, and the results have shown promising effects to correct pathophysiological processes related to dysregulated clocks [69,70,71,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…NOB is among a growing list of small molecules that were identified to directly target the circadian machinery [64,65,66,67,68]. A subset of these clock modifiers have been applied to disease models, and the results have shown promising effects to correct pathophysiological processes related to dysregulated clocks [69,70,71,72,73].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of proper clock maintenance is highlighted by linkages between circadian desynchrony and a variety of illnesses, including sleep and metabolic disorders, cardiovascular diseases, and cancer (1,2,(4)(5)(6)(7). This has fueled recent interest in the circadian clock as a therapeutic target (8)(9)(10)(11)(12). The nuclear receptors (NRs) REV-ERBα and -β, encoded by Nr1d1 and Nr1d2, link circadian rhythms and metabolism (1,13).…”
mentioning
confidence: 99%
“…Finally, novel small molecules have been identified that can modulate the circadian molecular system and are currently being investigated in the context of various neurological diseases 127,128 . Some of these small molecules had effects on circadian period, either lengthening or shortening, whereas others modulated circadian phase by delaying it, advancing it, or enhancing its amplitude 129,130 .…”
Section: Therapeutic Implications: Investigational Antiseizure Drugsmentioning
confidence: 99%
“…Others had a more direct effects on the circadian molecular system through interacting with and regulating the negative limbs of the system. Agonists and inverse agonists of RORs and REV‐ERBs as well as activators and inhibitors of CRYs have been identified 127,128 . None of these small molecules have been extensively investigated in the context of epilepsy.…”
Section: Therapeutic Implications: Investigational Antiseizure Drugsmentioning
confidence: 99%